Prawo karne jako narzędzie przeciwko wulgaryzacji języka - Marek Derlatka (Studia Paradyskie)
Profanity has been around for a long time, but the way it is treated in public is changing. Until a few decades ago, the use of such a word in public caused shame, embarrassment, and guilt. Today, part of the society accepts it with a smile, understanding and even appreciation. Does language culture require protection or should it be ensured by criminal law? The answers to the above questions may be different. Total freedom of speech advocates do not see the need to protect language, and certainly not by means of criminal law. Beauty lovers who appreciate the aesthetics and richness of language will stand up for its protection, even with the use of criminal law. Since the law is good and right, it should promote beautiful language by stigmatizing the use of indecent words in public places. Everyone should be anxious to follow the maxim of one of the greatest Roman orators - Marcus Fabius Quintilianus: speaking well is living well, being a good person.